Morphological Identification of Dragonflies Naiads (Odonata: Anisoptera) From Temporary Ponds in Basrah Province, South of Iraq: Identification of Dragonflies from Basrah, Iraq - Ahmed, Huda K.; Kareem, Dhia K. (Iraqi Journal of Aquaculture, 2024)
Dragonfly naiads of the Anisoptera species were collected from shallow ponds in Basrah Province, South of Iraq, between December 2017 and November 2018. The specimens were identified based on their morphological features, with special attention to the structure of the mandibles. A total of eight species were recorded, which included Anax parthenope from the Aeshnidae family, and seven species from the Libellulidae family: Crocothemis erythraea, C. servilia, Diplacodes trivialis, Orthetrum sabina, and Selysiothemis nigra. Naiads of two species, Diplacodes lefebveri and Sympetrum striolatium, were also observed in the study region for the first time.